EPI-CT: design, challenges and epidemiological methods of an international study on cancer risk after paediatric and young adult CT. (30th July 2015) - Bosch de Basea, Magda; Pearce, Mark S; Kesminiene, Ausrele; Bernier, Marie-Odile; Dabin, Jérémie; Engels, Hilde; Hauptmann, Michael; Krille, Lucian; Meulepas, Johanna M; Struelens, Lara; Baatout, Sarah; Kaijser, Magnus; et al.
Abstract: Computed tomography (CT) has great clinical utility and its usage has increased dramatically over the years. Concerns have been raised, however, about health impacts of ionising radiation exposure from CTs, particularly in children, who have a higher risk for some radiation induced diseases. Direct estimation of the health impact of these exposures is needed, but the conduct of epidemiological studies of paediatric CT populations poses a number of challenges which, if not addressed, could invalidate the results. The aim of the present paper is to review the main challenges of a study on the health impact of paediatric CTs and how the protocol of the European collaborative study EPI-CT, coordinated by the International Agency for Research on Cancer (IARC), is designed to address them. The study, based on a common protocol, is being conducted in Belgium, Denmark, France, Germany, the Netherlands, Norway, Spain, Sweden and the United Kingdom and it has recruited over one million patients suitable for long-term prospective follow-up. Cohort accrual relies on records of participating hospital radiology departments. Basic demographic information and technical data on the CT procedure needed to estimate organ doses are being abstracted and passive follow-up is being conducted by linkage to population-based cancer and mortality registries. The main issues which may affect the validity of study results include missing doses from other radiological procedures, missing CTs, confounding by CT indication and socioeconomic status and dose reconstruction. Sub-studies are underway to evaluate their potential impact. By focusing on the issues which challenge the validity of risk estimates from CT exposures, EPI-CT will be able to address limitations of previous CT studies, thus providing reliable estimates of risk of solid tumours and leukaemia from paediatric CT exposures and scientific bases for the optimisation of paediatric CT protocols and patient protection.